2009
DOI: 10.1007/s10517-009-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in the Kidneys of Rats with Postischemic Acute Renal Failure after Intrarenal Administration of Fetal Mesenchymal Stem Cells from Human Bone Marrow

Abstract: Chronic experiments on outbred albino rats were performed to compare the dynamics of histological signs for postischemic renal injury (90-min thermal ischemia) after intraparenchymal injection of cultured fetal MSC from human bone marrow. Functional indexes of the ischemic kidney were predetermined. In the early period after ischemia (day 4), administration of human bone marrow MSC was followed by the increase in blood flow in the microcirculatory bed and decrease in the degree of alteration in renal tubules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In addition, intraparenchymal injection of MSC increased blood flow in the microcirculatory bed and decreased the degree of alteration in renal tubules. In the delayed period, a protective effect was shown in the prevention of renal tubular death 20 . These results were favorable and asserted the potential use of SC in the functional recovery of an ischemic kidney.…”
Section: Applications Of Tissue Engineering and Stem Cells In The Genmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, intraparenchymal injection of MSC increased blood flow in the microcirculatory bed and decreased the degree of alteration in renal tubules. In the delayed period, a protective effect was shown in the prevention of renal tubular death 20 . These results were favorable and asserted the potential use of SC in the functional recovery of an ischemic kidney.…”
Section: Applications Of Tissue Engineering and Stem Cells In The Genmentioning
confidence: 77%
“…In the delayed period , a protective effect was shown in the prevention of renal tubular death. 20 These results were favorable and asserted the potential use of SC in the functional recovery of an ischemic kidney.…”
Section: Treatment Of Acute Renal Failurementioning
confidence: 87%
“…In un modello di ischemia renale acuta dello stesso animale, CS derivate da tessuto renale adulto hanno manifestato la capacità di differenziare sia in vitro che in vivo in cellule endoteliali e muscolari. Inoltre, iniezioni intraparenchimali di CS mesenchimali (CSM) hanno prodotto l'aumento del flusso sanguigno nella microcircolazione e diminuito il livello di alterazione dei tubuli renali (23,24). Anche i risultati ottenuti utilizzando le CS in modelli murini di insufficienza renale cronica sembrano promettenti.…”
Section: Insufficienza Renale Acuta E Cronicaunclassified
“…M esenchymal stem cells (MSCs) are progenitor cells that can be isolated from different tissues, in particular from bone marrow and adipose tissue [1][2][3]. Results obtained in our and other laboratories showed that direct injection of MSCs into the tissue is associated with a functional recovery of ischemic kidney [ 4 ] and heart [ 5 ]. In particular, MSCs protect against both chemical and ischemia-reperfusion damage and promote repair process in models of acute renal injury [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%